Predicting successful intended vaginal delivery after previous caesarean section: external validation of two predictive models in a Dutch nationwide registration‐based cohort with a high intended vaginal delivery rate. (18th February 2014) - Schoorel, ENC; Melman, S; van Kuijk, SMJ; Grobman, WA; Kwee, A; Mol, BWJ; Nijhuis, JG; Smits, LJM; Aardenburg, R; de Boer, K; Delemarre, FMC; van Dooren, IM; et al.
<x xml:space="preserve">Abstract</x> Objective To externally validate two models from the USA (entry‐to‐care [ETC] and close‐to‐delivery [CTD]) that predict successful intended vaginal birth after caesarean (VBAC) for the Dutch population. Design A nationwide registration‐based cohort study. Setting Seventeen hospitals in the Netherlands. Population Seven hundred and sixty‐three pregnant women, each with one previous caesarean section and a viable singleton cephalic pregnancy without a contraindication for an intended VBAC. Methods The ETC model comprises the variables maternal age, prepregnancy body mass index (BMI), ethnicity, previous vaginal delivery, previous VBAC and previous nonprogressive labour. The CTD model replaces prepregnancy BMI with third‐trimester BMI and adds estimated gestational age at delivery, hypertensive disease of pregnancy, cervical examination and induction of labour. We included consecutive medical records of eligible women who delivered in 2010. For validation, individual probabilities of women who had an intended VBAC were calculated. Main outcome measures Discriminative performance was assessed with the area under the curve (AUC) of the receiver operating characteristic and predictive performance was assessed with calibration plots and the Hosmer–Lemeshow (H‐L) statistic. Results Five hundred and fifteen (67%) of the 763 women had an intended VBAC; 72% of these (371) had an actual VBAC. The AUCs of the ETC and CTD models were 68% (95% CI 63–72%) and 72% (95% CI 67–76%), respectively. The H‐L statistic showed a P‐value of 0.167 for the ETC model and P = 0.356 for the CTD model, indicating no lack of fit. Conclusion External validation of two predictive models developed in the USA revealed an adequate performance within the Dutch population.